What drives FDI from non-traditional sources? A comparative analysis of the determinants of bilateral FDI flows - Maximiliano Sosa Andrés; Peter Nunnenkamp; Matthias Busse (Kiel Institute for the World Economy (IfW), 2012)
Non-traditional source countries of FDI play an increasingly important role, notably in developing host countries. This raises the question of whether the location choices differ systematically between traditional and non-traditional source countries. We perform Logit and Poisson Pseudo Maximum Likelihood estimations to assess the determinants of bilateral FDI flows. We find that economic geography variables are more relevant for FDI from nontraditional sources. The risk aversion of non-traditional investors is not consistently weaker than that of traditional investors. Resource abundance and superior technology in the host countries represent minor pull factors of FDI from non-traditional sources.
Keywords: F21; 330; FDI flows; types of FDI; source-host country pairs; location choices; gravity-type models